2020
DOI: 10.1186/s13102-020-00202-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Norm-based Intervention with Observable Behaviour on Physical Activity among Adolescents: A Randomized Controlled Trial

Abstract: Background: The rising prevalence of childhood obesity in developing and developed countries poses a major public health challenge to policy makers and an effective strategy to promote physical activity among adolescents is warranted. This study aimed to evaluate the effectiveness of providing descriptive norms messages with personal identification in promoting physical activity among adolescents by measuring step counts via a randomized controlled trial (NCT03081013). Methods: A total of 311 participants aged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The step counts of those in the descriptive norm condition also compared favorably to those in the control condition, although this difference was not significant. By contrast, Lee et al (2020) found minimal evidence that participants who received weekly text messages reporting other participants’ step counts increased their own step counts over a 16-week period. It should be noted, however, that these researchers’ primary focus was on whether the normative influence is greater when the normative referent is onymous versus anonymous, and thus a control group not exposed to norm messages was not included.…”
Section: Norms and Physical Activity Behaviorsmentioning
confidence: 80%
“…The step counts of those in the descriptive norm condition also compared favorably to those in the control condition, although this difference was not significant. By contrast, Lee et al (2020) found minimal evidence that participants who received weekly text messages reporting other participants’ step counts increased their own step counts over a 16-week period. It should be noted, however, that these researchers’ primary focus was on whether the normative influence is greater when the normative referent is onymous versus anonymous, and thus a control group not exposed to norm messages was not included.…”
Section: Norms and Physical Activity Behaviorsmentioning
confidence: 80%